Visual storytelling and cultural connection in GCC social media advertising - Mohamed, Khaled Mostafa M. (Frontiers in Communication, 2025)
IntroductionSocial media has transformed brand communication in the GCC, making culturally relevant visual storytelling essential for effective engagement.MethodsA cross-sectional online survey was conducted among 231 participants across the six GCC countries to examine perceptions of visual storytelling in social media advertising.ResultsFindings revealed a strong preference for culturally aligned, narrative-driven visual content on platforms like Instagram and TikTok. Key elements such as color, authentic imagery, and cultural symbols significantly enhanced consumer trust and engagement.DiscussionThe study underscores the importance of culturally sensitive visual narratives in enhancing brand credibility and consumer loyalty in GCC markets.